Accounting Applications in the Implementation of Entrepreneurs' Financial Management in Indonesia - Susilo, Tri Achmad Budi; Susyadi, Susyadi; Widjaja, Ratna A Marhaenita; Yuliadi, Praptop; Meranti, Inud Danis Ikhwan; Sailau, Ana Roza Widiamay (Universitas Kristen Cipta Wacana, 2024)
This article aims to describe technological advances in the field of accounting that are implemented using applications. Accounting comes from a foreign language, Accounting, which means to calculate or account. Accounting is used in various business activities as a basis for preparing information and making decisions for business. The research method used in this research is a descriptive qualitative approach with secondary data methods mainly through literature studies obtained from journals or supporting articles, as well as various news that are aligned with the needs of the article. There are 5 forms of companies in their objectives and performance: Production companies, trading companies, service companies, sole proprietorships and partnership companies. In the development of technology, especially applications in the field of accounting, this article reviews 12 accounting applications, including: Accounting Software Recommendations: MASERP by MAS Software, Jurnal, Accurate, Zahir, Hashmicro, EPICOR, SAP Business One, Oracle ERP Cloud Microsoft Dynamics AX, Xero, QuickBooks and FreshBooks.